Cypermethrin inhibits interleukin-6-induced androgen receptor transactivation through signal transducer and activator of transcription 3. (22nd November 2017) - Zhou, Ji-Long; Ding, Zhen; Ge, Xing; Shi, Qiao-Mei; Wang, Heng-Xue; Chen, Gang; Li, Meng-Xue; Wang, Hui; Ju, Qiang; Wang, Qi; Zhang, Jin-Peng; Zhang, Mei-Rong; et al.
Abstract: The insecticide cypermethrin has been considered as an endocrine-disrupting chemicals (EDCs) with anti-androgenic activity by interfering with interleukin-6 (IL-6)– induced ligand-independent AR signaling. The purpose of this study was to clarify whether the signal transducer and activator of transcription 3 (STAT3) was involved in the antagonism effect of cypermethrin. In this study, the Western blot was to test the level of STAT3 phosphorylation and the mammalian two-hybrid assay was developed to assess the AR–STAT3 interaction. The date showed that IL-6 increased the phosphorylation level of STAT3 and enhanced the AR–STAT3 interaction. Cypermethrin did not affect the phosphorylation level of STAT3 induced by IL-6, while suppressed the AR-STAT3 interaction induced by IL-6 significantly at the concentration of 10 −5 M ( p < 0.05). The study indicates cypermethrin inhibits IL-6–induced AR signaling by suppressing the interaction between the AR and STAT3. We provide a novel mechanism of cypermethrin-mediated antagonism on IL-6–induced AR activation associated with STAT3.